1997
DOI: 10.1136/vr.140.5.124
|View full text |Cite
|
Sign up to set email alerts
|

Insemination of cattle with semen from a bull transiently infected with pestivirus

Abstract: When 73 heifers (60 of which were seronegative to pestivirus) were inseminated with pestivirus-contaminated semen from a transiently infected bull, the conception rate to a single insemination was found to be normal (65 per cent). Only three animals became systemically infected, as determined by viraemia and seroconversion. Pestivirus was isolated from the reproductive tracts of two of these heifers when they were slaughtered 42 or 43 days after insemination. Although the initial incidence of infection was low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 14 publications
0
20
0
3
Order By: Relevance
“…Munoz-Zanzi et al [29] found the CR for BVDVinfected heifers in a herd to be 67.3%. Kirkland et al [22] stated that when they fertilized 73 heifers with sperm from a bull carrying BVDV, the average CR in the heifers was 65%, the same as the CR of the uninfected heifers. However, although there were no BVDV (Ag+/Ab+) pregnant animals in our study, a statistically significant difference (p<0.0001) was determined between the CRs of the BVDV (Ag+/Ab+) and uninfected heifers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Munoz-Zanzi et al [29] found the CR for BVDVinfected heifers in a herd to be 67.3%. Kirkland et al [22] stated that when they fertilized 73 heifers with sperm from a bull carrying BVDV, the average CR in the heifers was 65%, the same as the CR of the uninfected heifers. However, although there were no BVDV (Ag+/Ab+) pregnant animals in our study, a statistically significant difference (p<0.0001) was determined between the CRs of the BVDV (Ag+/Ab+) and uninfected heifers.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have investigated the effect of BVDV infection on reproductive parameters such as conception rate (CR) [19,34], and it has been concluded that BVDV has a negative effect on the fertility of cows and heifers [11], with field studies reporting up to a 44% decline in CR [23,40]. However, some experimental and field studies have found that BVDV infection does not affect the CR of heifers [22,26].In this study, blood serum and leukocyte samples were collected from 400 heifers in tie-stall barns in the Burdur Province area of SW Turkey. All had been fertilized for the first time.…”
mentioning
confidence: 99%
“…190 In a group of heifers experimentally inseminated with contaminated semen from an acutely infected bull, approximately 5% became systemically infected. 191 While this initial rate of infection was low, it was sufficient for further transmission to susceptible heifers and maintenance of BVDV in the herd. 191 Under field conditions, AI with semen from two acutely infected bulls resulted in infections rates in exposed cows of 15.4% and 1.8%, respectively.…”
Section: Infections Of Bullsmentioning
confidence: 99%
“…191 While this initial rate of infection was low, it was sufficient for further transmission to susceptible heifers and maintenance of BVDV in the herd. 191 Under field conditions, AI with semen from two acutely infected bulls resulted in infections rates in exposed cows of 15.4% and 1.8%, respectively. 192 Semen from PI bulls can contain large quantities of BVDV (10 3 -10 7 CCID 50 /mL).…”
Section: Infections Of Bullsmentioning
confidence: 99%
“…Kirkland et al [35] of the embryos as recommended by IETS were not effective in rendering IVF embryos free from M. bovis and M. bovigenitalium.…”
Section: Bovine Viral Diarrhoea Virus (Bvdv)mentioning
confidence: 99%